(untitled) (Medical Forum Monthly, 2022)
Objective: We aimed to analyze the frequency and adverse maternal and perinatal outcomes of adolescent pregnancy in a tertiary care setting. Study Design: retrospective case-control study Place and Duration of Study: This study was conducted at D. Ruth K. M. Pfau Civil Hospital Karachi from Nov, 2020 to Oct, 2021. Materials and Methods: We recruited 921 women delivering between 15 to 35 years during this period. Participants were divided into two groups as adolescents and adults according to their age. First group comprised of adolescents (n) aged between 15-19 years and second consisted of adults (2n) between 20-35 years as control. Case records were reviewed and information collected on a specially designed proforma. This data included socio demographic characteristics, birth mode and maternal and fetal outcomes. Data stored and analyzed by SPSS version 21. Results: Our results revealed frequency of teenage pregnancies as 9.5%. Majority of these adolescents were aged between 17-19yrs (96.7%), were urban residents (60.9%), un-booked (67.7%) and married (96.4%). However 3.6% comprised of unmarried girls also. About a quarter delivered by cesarean section (24.4%). Significant fetomaternal outcomes included anemia (35.8%), preterm delivery (25.4%), PPROM (9.4%), sepsis (7.2%), non-progress of labor (8.1%), Eclampsia (4.6%), stillbirth (13.4%) and neonatal deaths (7.2%). Conclusion: Adolescent pregnancy poses serious health risks and is associated with adverse fetomaternal outcomes like anemia, preterm delivery, sepsis, eclampsia and poor perinatal outcomes.